2017
DOI: 10.1093/neuros/nyx417.138
|View full text |Cite
|
Sign up to set email alerts
|

138 Endoscopic Endonasal Skull Base Surgery in Pediatric Patients and Impact on Midface Growth

Abstract: INTRODUCTION Cranial base development plays a large role in anterior and vertical maxillary growth through age 7, and the effect of early endonasal cranial base surgery on midface growth is unknown. We present our experience with pediatric endoscopic endonasal surgery and long-term midface growth. METHODS This is a retrospective review (2000-2016). Pediatric patients were grouped by age at first endoscopic endonasal skull bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…4 8 9 Parasher et al and Chen et al demonstrated that the age at which endoscopic endonasal surgery (EES) is performed does not affect midface growth or craniofacial development. 10 11 Although endoscopic approaches have many benefits, they are not without potential complications including cerebrospinal fluid leak, meningitis, cranial neuropathy, and pneumocephalus. 4 In a recent study, Lenze et al showed a similar complication profile when comparing open and endoscopic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…4 8 9 Parasher et al and Chen et al demonstrated that the age at which endoscopic endonasal surgery (EES) is performed does not affect midface growth or craniofacial development. 10 11 Although endoscopic approaches have many benefits, they are not without potential complications including cerebrospinal fluid leak, meningitis, cranial neuropathy, and pneumocephalus. 4 In a recent study, Lenze et al showed a similar complication profile when comparing open and endoscopic approaches.…”
Section: Introductionmentioning
confidence: 99%